2019
DOI: 10.1371/journal.pone.0223260
|View full text |Cite
|
Sign up to set email alerts
|

A super-SILAC based proteomics analysis of diffuse large B-cell lymphoma-NOS patient samples to identify new proteins that discriminate GCB and non-GCB lymphomas

Abstract: Diffuse large B-cell lymphoma—not otherwise specified (DLBCL-NOS) is a large and heterogeneous subgroup of non-Hodgkin lymphoma. DLBCL can be subdivided into germinal centre B-cell like (GCB) and activated B-cell like (ABC or non-GCB) using a gene-expression based or an immunohistochemical approach. In this study we aimed to identify additional proteins that are differentially expressed between GCB and non-GCB DLBCL. A reference super-SILAC mix, including proteins of eight B-cell lymphoma cell lines, was mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In a recent proteomic study [12], which also could separate ABC and GCB patients by their global protein profile in FFPE samples (n ¼ 42), we could significantly reproduce 6 of 8 proteins in their separating 8-protein signature. Three other smaller studies have also performed proteomic COO analyses in DLBCL patients [9][10][11]; however, they could not reproduce well-known COO proteins and even if there was some minor overlap, none of their top-upregulated proteins in the different subgroups were upregulated in our study. In summary, we believe that the reliability of our protein identification and expression patterns is high, judging by the overlap both of the proteins identified by the Deeb and Reinders studies and most of the corresponding genes separating the ABC subtype from GCB in the Lymph2cx gene chip, as well as a reproduction of some of the differentially regulated proteins using immunohistochemical staining.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In a recent proteomic study [12], which also could separate ABC and GCB patients by their global protein profile in FFPE samples (n ¼ 42), we could significantly reproduce 6 of 8 proteins in their separating 8-protein signature. Three other smaller studies have also performed proteomic COO analyses in DLBCL patients [9][10][11]; however, they could not reproduce well-known COO proteins and even if there was some minor overlap, none of their top-upregulated proteins in the different subgroups were upregulated in our study. In summary, we believe that the reliability of our protein identification and expression patterns is high, judging by the overlap both of the proteins identified by the Deeb and Reinders studies and most of the corresponding genes separating the ABC subtype from GCB in the Lymph2cx gene chip, as well as a reproduction of some of the differentially regulated proteins using immunohistochemical staining.…”
Section: Discussionmentioning
confidence: 83%
“…Instead, methods to directly study the global protein expression and interaction could bring new knowledge regarding the pathophysiology of DLBCL subgroups. Some global protein expression studies using a proteomic approach where non-GCB or ABC patients are compared to controls or their GCB counterpart have been published [8][9][10][11][12]. Even though these studies show promising results, the results have been diverging which at least partly could be explained by the use of different techniques and perhaps foremost the low total number of included patients (ranging from a total of 6-42 patients).…”
Section: Introductionmentioning
confidence: 99%
“…For a deeper characterization, LC-MS strategies are commonly used. Thus, van der Meeren et al [87] profiled the two subtypes of DLBCL (GCB and non-GCB), analyzing more than 4200 proteins of which 37 were found significantly differentially expressed between the two subtypes. Validation of these markers revealed that the expression of glomulin protein was higher in GCB-DLBCL patients, whereas ribosomal protein L23 was a biomarker for non-GCB-DLBCL individuals.…”
Section: Proteomics Studies On Diffuse Large B Cell Lymphoma (Dlbcl)mentioning
confidence: 99%
“…(2) bias due to deviations from the intended intervention; (3) bias due to missing outcome data; (4) bias in the measurement of the outcome; and (5) bias in the selection of the reported results (Figure S3A,B). The results of the risk of bias assessment revealed one study with a high risk [48], seven with a low risk [27,[49][50][51][52][53][54], and nineteen with a moderate risk of bias [26,[55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72].…”
Section: Assessment Of the Risk Of Bias In Individual Studiesmentioning
confidence: 99%